(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe epidemiological characteristics and identify factors associated with dermatophytosis among patients at Can Tho University of Medicine and Pharmacy Hospital. Methods: A cross-sectional study was conducted. Dermatophytosis was diagnosed using direct microscopy and culture on Dermatophytes Test Agar. Epidemiological characteristics and potential associated factors were collected using a structured questionnaire. Multivariable logistic regression analysis was performed to identify independent associated factors. Results: The prevalence of dermatophytosis among patients with suspected fungal skin lesions was 26%. Patients aged ≥ 60 years had a significantly higher prevalence compared with those aged <20 years (p = 0.03). The prevalence was higher in males than females (27.8% vs. 24.2%), but the difference was not statistically significant. Patients living in rural areas had a significantly higher prevalence than those living in urban areas (p < 0.05). Multivariable analysis showed that rural residence (adjusted odds ratio AOR = 2.23), corticosteroid use (AOR = 5.90), and wearing damp clothing (AOR = 6.28) were independently associated with dermatophytosis (p < 0.05). Conclusions: Dermatophytosis remains prevalent, particularly among older adults. Rural residence, inappropriate corticosteroid use, and damp clothing are major independent factors associated with infection, highlighting the importance of behavioral and environmental interventions for prevention.